Development Scenario of Collaborative Management at Bantimurung Bulusaraung National Park, South Sulawesi Province - Abd. Kadir Wakka; San Afri Awang (Jurnal Penelitian Kehutanan Wallacea, 2017)
Collaborative management is the most appropriate strategy in an effort to accommodate the interests of local communities in the management of protected areas. Success of collaborative management is highly dependent on the extent of identification of key factors for strategy success to compile scenarios into operational recommendations. This study aimed to formulate a collaborative management strategy for Bantimurung Bulusaraung National Park (Babul NP) based on scenarios that may occur in the future. The study was conducted by observation, interviews and questionnaires to a number of expert informants and literature studies. Data was analyzed using a prospective analysis. The results showed that the development of collaboration in the future is an optimistic scenario with the increasing awareness of the interdependence of interests, improving human resource competencies, collaboration, the ability to build networks with other stakeholders, improving the ability to coordinate with relevant stakeholders and the ability to establish cooperation with them and the adequation of goverment policies to give a place to people in the utilization of the Babul NP. Application of collaborative development scenario is expected to improve Babul NP management.